INVESTIGATION OF TEMPERATURES AND HOLDING TIMES ON HIGH-STRENGTH LOW-ALLOY STEEL FOR TANK TRACK LINKS - Selly Septianissa; Komang Widhi Widantha; Muhamad Waldi (Logic : Jurnal Rancang Bangun dan Teknologi, 2024)
In Indonesia, the reliance on foreign countries for military components persists, including tank track links which are crucial for combat vehicles. These components require mechanical properties such as wear resistance and toughness to ensure high safety standards. High Strength Low Alloy (HSLA) steel is used, necessitating precise composition and appropriate heat treatment processes. This study varied compositions and heat treatments to achieve desired properties, producing prototypes with five predetermined compositions. The heat treatment process involves initially heating the samples to 860°C for 30 minutes for uniformity, followed by various treatments including quenching in oil, normalizing, and multiple cycles of quenching with tempering at different temperatures and durations to refine microstructure and adjust hardness of the alloy. Results showed optimal mechanical properties in composition no. 4 after normalizing with a blower, achieving a hardness of 31 HRC. This research aimed to optimize mechanical performance during operational conditions through variations in temperatures and holding times.